Analisis Pemberdayaan Karyawan dan Pengaruhnya Terhadap Komitmen Organisasional - Eli Achmad Mahiri (Journal of Innovation in Management, Accounting and Business, 2022)
This study aims to determine employee empowerment, and organizational commitment of permanent employees of PDAM Majalengka Head Office. In addition, the purpose of this study is to determine how much influence employee empowerment has on organizational commitment. The research method used is survey research with a descriptive verification approach. The analytical tools used in this research are correlation, coefficient of determination, and hypothesis testing for partial test using t test and simultaneous test using F test. The results show that employee empowerment has a significant effect on organizational commitment, meaning that employees are empowered as best as possible compared to other employees. which is felt to be in accordance with what they expect it will increase organizational commitment in employees.